MAX AND HIS FURY SPELLS: A CASE OF BILATERAL PHEOCHROMOCYTOMA WITH MAX-ASSOCIATED PATHOGENIC GENE MUTATION - Low, Chee Koon; Krishnabalan, Kausalyaa; Nasruddin, Azraai Bahari; Hussein, Zanariah (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Understanding of the genetic pathophysiology of pheochromocytomas and paragangliomas (PPGLs) syndrome has advanced significantly over the past two decades. PPGLs entail three specific disease clusters based on their underlying genetic alterations. Pathogenic variants affecting the Myelocytomatosis-Associated factor X (MAX) gene predispose to PPGLs occurring at a younger age. More than half develop bilateral pheochromocytomas with metastatic disease seen in 20 percent of patients. CASE This is the first case report in Malaysia describing a young male with bilateral pheochromocytoma secondary to a novel pathogenic variant identified in the MAX gene. A 28-year-old male was found to be hypertensive during a dental procedure. Four months later, he was hospitalized due to palpitations and treated for rhabdomyolysis with non-ST-elevation myocardial infarction. Echocardiography did not show cardiomyopathy and coronary angiography was normal. Endocrine evaluation showed an elevated 24- hour urine metanephrine level of 38.8 micromol/day (24 times ULN), urine normetanephrine level of 30.8 micromol/day (14.5 times ULN), and urine methoxytyramine level of 6.5 micromol/day (3.6 times ULN). Adrenal CT revealed bilateral lipid-poor adrenal masses (Left: 7.1 x 7.5 x 7.4 cm; and right: 2.0 x 1.1 x 1.8 cm). There was no family history of multiple endocrine neoplasia or Von-Hippel. Lindau syndrome. Thyroid ultrasonography and retinal examination were normal. Our clinical dilemma was whether both adrenal lesions were pheochromocytomas. Gallium-68 PET/CT showed significant uptake in the left adrenal mass, indeterminate on the right. A genetic study identified a pathogenic variant c.234_235dup in exon 4 of the MAX gene. Henceforth, bilateral pheochromocytoma was highly considered. Because of the metastatic potential of the disease, he underwent bilateral adrenalectomy. CONCLUSION Each PPGLs cluster has a unique clinical, biochemical and imaging phenotype which can help clinicians deliver a personalized treatment strategy for patients with PPGLs. Precision medicine approach to PPGLs should be more widely available and become the standard of care in our nation.